Pembelajaran Berbasis Proyek Untuk Mengembangkan Karakter Mahasiswa - Ismail Ismail; Abdul Muis (Seminar Nasional LP2M UNM, 2019)
The imbalance in the orientation of educational goals in Indonesia is considered as the cause of the failure of character formation. The learning process in class is only concerned with academic achievement and ignores the practice of good behavior. Therefore, this research was conducted with the aim of developing the character and academic achievements of students through Project Based Learning (PjBL) in plant physiology courses. The study was designed as a pre-experiment using Single-Group Pretest and Posttest Design. Students are given a pretest before being given a learning treatment by applying PjBL and thereafter given a posttest. The random sampling technique was used to select one of three classes of participants in plant physiology courses with a total of 36 students. Student character observation sheets and learning achievement tests are used as instruments. Descriptive analysis, t-test, and N-Gain are used in data analysis. The results revealed that the application of PjBL in plant physiology courses can develop the character of discipline and responsibility and student learning outcomes. This study recommends that lecturers in higher education institutions apply the PjBL model among learner-centered learning models for the purpose of character development and academic achievement